Uma sequência didática para o uso do multímetro como uma ferramenta na aprendizagem de medidas elétricas no ensino médio - Souza, Roberto Wanderley de (Universidade Federal Rural do Semi-Árido, 2020)
The work deal to show through experimentation a didactic sequence to be carried out by physics teachers with the aid of the multimeter measurement instrument, as an alternative tool in the learning of electrical measures studied in the didactic content of physics in high school. Thus, allowing this technology, it can assist in the development of competences and skills of investigation and understanding of measurements, favoring the recognition of the use of demonstrative experiences as a motivating instrument for students. The product was applied to a third-year-high school class at a school in the Areia Branca-RN city. A pretest questionnaire was applied as a way to guide the work of the educational product to be applied and a post-test with objective and open questions. A didactic script was made available containing expository classes, demonstrations and experimental practice activities that are easy to assemble with lamps and resistors, using the aid of a digital multimeter, which allows the teacher to take the student to solve proposed problems. The students made the measurements of current, resistance and potential difference using the multimeter as a learning aid tool. In the end, they reported the experience of using the multimeter in physics classes
Keywords: Multímetro; Eletricidade; Ensino em física; Multimeter; Electricity; Physics teaching; CIENCIAS EXATAS E DA TERRA::FISICA